Singular quasilinear elliptic systems involving gradient terms. (October 2020) - Candito, Pasquale; Livrea, Roberto; Moussaoui, Abdelkrim
Abstract: In this paper we establish the existence of at least one smooth positive solution for a singular quasilinear elliptic system involving gradient terms. The approach combines the sub-supersolutions method and Schauder's fixed point theorem.